Beyond the state The colonial medical service in British Africa - Greenwood, Anna (Studies in Imperialism, 2015)
The Colonial Medical Service was the personnel section of the Colonial Service, employing the doctors who tended to the health of both the colonial staff and the local populations of the British Empire. Although the Service represented the pinnacle of an elite government agency, its reach in practice stretched far beyond the state, with the members of the African service collaborating, formally and informally, with a range of other non-governmental groups. This collection of essays on the Colonial Medical Service of Africa illustrates the diversity and active collaborations to be found in the untidy reality of government medical provision. The authors present important case studies covering former British colonial dependencies in Africa, including Kenya, Malawi, Nigeria, Tanzania, Uganda and Zanzibar. They reveal many new insights into the enactments of colonial policy and the ways in which colonial doctors negotiated the day-to-day reality during the height of imperial rule in Africa.